Spectral characteristics analysis of rocks and ores based on the generalized effective medium theory of induced polarization - Wang, Shu; Wang, Tianyi; Yang, Jin (Frontiers in Earth Science, 2023)
To study the electrical characteristics of rocks and ores, two- and three-phase medium models with different mineral contents, attenuation coefficients, relaxation times, and ellipticities were established based on the generalized effective medium theory of induced polarization (GEMTIP) model and the Debye decomposition method. Furthermore, the corresponding program was written for numerical simulation, and the complex resistivity (CR) spectral characteristics and relaxation time distribution (RTD) characteristics were analyzed. At the same time, seven representative ore samples from different mining areas were selected, their structural compositions were observed, and their CR was measured to obtain the variation characteristics and Nyquist curves of ore phase spectra. The differential evolution (DE) algorithm was employed to write a curve parameter fitting program based on which parameter fitting was performed for the theoretical model and the measured curves of ore samples. The physical and electrical parameters of the curves were obtained, and the variation characteristics of each parameter were analyzed. The GEMTIP model could be adopted to further study the induced polarization (IP) anomaly from the structural and electrical properties of rocks and ores, which has important guiding significance for energy resource exploration, deep prospecting, and environmental investigation by electrical (magnetic) methods.